Saberes docentes e trajetos formativos de professores de língua portuguesa da EPT - Gonçalves, Paula Joseane Rocha (2021)
This research is linked to the line of research Teacher Training for Professional Education of the Master in Professional and Technological Education at UFSM and to the Group of Studies and research in Initial and Continuing Teacher Training - Magma. To do so, we started with the following research question: How are the teaching knowledge constituted and in what way the formative paths are singularized by the experiential knowledge of the Portuguese Language teachers in the EBPT of a Federal Institute of Rio Grande do Sul? Is there any impact of these paths on the praxis of these teachers? Seeking to answer this question, this dissertation presents a research carried out with eight educators, which aimed to know the training paths and teaching knowledge of teachers of Portuguese Language and Brazilian Literature, working in Integrated Technical courses at the medium level of Professional and Technological Education (EPT), in the sense of analyzing how training paths and teaching knowledge influence their pedagogical practices. We seek to know their training paths, their teaching knowledge, the representations they have of teaching as well as the educational practices developed by them and that leverage the teaching of LPLB. For this, the methodological choice was qualitative research. The inclusion criteria were to be an effective teacher in the area of Letters and to be working with the discipline of LPLB in the integrated technical courses at the secondary level. As for the production of data, the interviews were of the semi-structured type, which allows for greater interaction between the interviewer and the interviewee. For data analysis, Content Analysis according to Bardin was used. It was possible to realize that the training paths of employees are full of professional choices and that experiential knowledge is essential for the success of educational practices in the classroom. In addition, LPLB teaching is based on proposals for meaningful activities for learners. Although the professors affirm that they have learned in practice to work with Integrated High School, it is important to emphasize that universities must qualify future teachers for work in EPT.